2008
DOI: 10.1007/s10566-008-9058-2
|View full text |Cite
|
Sign up to set email alerts
|

Who Stays in Treatment? Child and Family Predictors of Youth Client Retention in a Public Mental Health Agency

Abstract: The present study examined possible predictors of youth client retention in therapy in a large community-based sample. We used several conceptualizations of retention, including (a) "intake retention" (i.e., returned to treatment after intake session); (b) "mutual termination" (i.e., termination agreed upon by family and therapist), (c) "mean treatment duration" (i.e., completing the mean number of sessions in the agency), and (d) "total treatment duration" (i.e., total number of sessions). Archival data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
6
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 50 publications
4
115
6
4
Order By: Relevance
“…Interestingly, despite these well-documented differences between children mandatorily and voluntarily referred to treatment, studies that have directly compared treatment engagement between these two groups have found no statistically significant differences (Inueste-Montes & Montes, 1988;Koverola et. al, 2007;Miller, Southam-Gerow & Allin, 2008).…”
Section: Children's Entry Into Treatmentmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, despite these well-documented differences between children mandatorily and voluntarily referred to treatment, studies that have directly compared treatment engagement between these two groups have found no statistically significant differences (Inueste-Montes & Montes, 1988;Koverola et. al, 2007;Miller, Southam-Gerow & Allin, 2008).…”
Section: Children's Entry Into Treatmentmentioning
confidence: 98%
“…Relatively few studies of treatment engagement include children (Kazdin & Mazurick, 1994;Miller, Southam-Gerow & Allin, 2008). This is problematic because, as Costello et.…”
Section: Problems With the Existing Literature On Children's Engagemementioning
confidence: 99%
See 2 more Smart Citations
“…Investigação metanalítica 7 sobre interrupção da psicoterapia revisou 125 estudos e encontrou que somente 16 envolviam amostras compostas por crianças. Desde essa revisão, o número de estudos realizados em centros comunitários de saúde mental com crianças continua escasso 8 . No entanto, entender o perfil da clientela que não adere à psicoterapia psicanalítica seria um primeiro passo na elaboração de medidas para tentar engajar essas crianças e seus responsáveis em psicoterapia; também auxiliaria na revisão de critérios de indicação e contraindicação para essa modalidade terapêutica, a fim de atualizar as ferramentas técnicas para a demanda atual de crianças em psicoterapia.…”
Section: Introductionunclassified